The plot in Isaiah 40-55 - SL Stassen (Acta Theologica)
In the past a great deal of confusion existed among scholats concerning the roles of the different characters in the "literay drama" of Isaiah 40-55. A good example of this confusion is the question of whether the nations form part of Yahweh's invitation to salvation or not. Another example is the different roles allocated to the Ebed Yahweh and the issue of whether he represents Israel, or the prophet, or Cyrus, or an entirely dffferent person. This confusion is partly due to the fact that the plan/plot of the "drama", as it unfolds in Isaiah 40-55, has not yet been unravelled successfully. A drama usually has a specific plan according to which each character acts and relates to the other characters. In the same manner Isaiah 40-55 has a plot in which each character has their specific roles accotding to which they act and relate to each other.  As in other dramas the plot in Isaiah 40-55 develops into a climax in certain aspects, but to an anti-cllimax in others.